2020
DOI: 10.1002/ajmg.a.61983
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum in multiple families with primary COQ10 deficiency

Abstract: Coenzyme Q 10/ COQ 10 , an essential cofactor in the electron-transport chain is involved in ATP production. Primary COQ 10 deficiency is clinically and genetically a heterogeneous group of mitochondrial disorders caused by defects in the COQ 10 synthesis pathway. Its mode of inheritance is autosomal recessive and it is characterized by metabolic abnormalities and multisystem involvement including neurological features. Mutations in 10 genes have been identified concerning this group of diseases, so far. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 53 publications
0
14
1
Order By: Relevance
“…Hashemi et al reported a case in which one of two affected siblings showed cerebellar atrophy and white matter abnormalities on T2 and FLAIR brain MRI sequences [ 24 ]. In another individual, brain MRI at the age of four months revealed bilateral increased signal intensities in the putamen and cerebral cortex (Leigh pattern) [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hashemi et al reported a case in which one of two affected siblings showed cerebellar atrophy and white matter abnormalities on T2 and FLAIR brain MRI sequences [ 24 ]. In another individual, brain MRI at the age of four months revealed bilateral increased signal intensities in the putamen and cerebral cortex (Leigh pattern) [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…MR spectroscopy showed a lactate peak [ 41 ]. A nine-year-old girl with neurological symptoms and COQ7 deficiency referred to by Hashemi et al showed no gross abnormalities in MRI of the brain and spine [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“… 9 Responses to oral supplementation are variable and may be tissue dependent. 5 - 7 , 10 , 11 CoQ 10 treatment has not resulted in a long-term improvement in COQ7 phenotypes, 6 , 7 , 10 , 11 but advances in methods to solubilize CoQ 10 may lead to better outcomes in the future. 9 No experiments to rescue metabolic function of cultured fibroblasts from the affected siblings were performed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…CoQ 10 deficiencies are frequently treated with a high-dose oral supplementation of CoQ 10 or CoQ 10 precursor molecules that bypass the relevant genetic alteration, with 2,4-dihydroxybensoic acid as a notable example for COQ7 -related CoQ 10 deficiency. 5 - 7 , 9 - 11 However, the efficacy and safety of 2,4-dihydroxybensoic acid has recently been called into question. 9 Responses to oral supplementation are variable and may be tissue dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the spectrum of symptoms of encephalopathy, intellectual disability, seizures, and muscle involvement has been described in patients with variants responsible for other primary coenzyme Q10 deficiency ( COQ2 , COQ4 , COQ6 , COQ7 , COQ9 ) as well as in patients with COQ8A -ataxia. In the case of patients who do not present the ataxia simplex phenotype, and due to similarity in laboratory findings and a wide spectrum of overlapping of other neurological symptoms, it may be hard to differentiate among primary coenzyme Q10 deficiency without genetic testing [ 4 , 72 ].…”
Section: Differential Diagnosis Of Other Mitochondrial Disorders Pres...mentioning
confidence: 99%